ACELE KAMULAŞTIRMA - (:unkn) unknown (My University, 2013)
Acele Kamulaştırma, Kamulaştırma Kanunun 27. maddesinde düzenlenen ve belirli koşulların varlığında kullanılan olağanüstü kamulaştırma usulüdür. Acele Kamulaştırmanın yapılabileceği hallerin arasında bulunan, Aceleliğine Bakanlar Kurulunun vermiş haller, objektif esaslara dayalı olmaması nedeniyle üzerinde ciddi tartışmalar yapılmaktadır. Bu çalışmada, Danıştayın yaklaşımıyla birlikte Aceleliğine Bakanlar Kurulunun karar verdiği hallere açıklık getirilmeye çalışılacaktır.

Urgent expropriation is regulated at the 27. Article of Expropriaton Act and outstanding expropriation procedure is used in the presence of certain conditions. One of the urgent expropriation case where can be applied: urgent cases that the Council of Ministers will decide. However, this situation has been criticized. approach to the subject the Council of State will be studied and will be explained in this manner urgent expropriation.
Keywords: Hukuk